Happy Hypoxia Pada Coronavirus Disease - Shianata, Chrisshania M.; Engka, Joice N. A.; Pangemanan, Damajanty H. C. (UNIVERSITAS SAM RATULANGI, 2021)
Abstract: COVID-19 is a multifaceted disease with respiratory failure as a common manifestation. SARS-CoV-2 primarily attacks respiratory epithelial cells via adhesion to Angiotensin-Converting Enzyme 2 (ACE-2), patients may develop a mild to severe inflammatory response and acute lung injury. Several reports suggest that many patients appear to show less respiratory effort and experience less dyspnea when exposed to acute respiratory failure and hypoxemia, a phenomenon called â€œhappy hypoxiaâ€ or â€œsilent hypoxemiaâ€. This causes COVID-19 patients to be unaware of the hypoxemia in their bodies and fail to seek help which leads to death. The purpose of this study is to discover the process of Happy Hypoxia in COVID-19 patients. The materials and methods used are literature reviews with data from PubMed, ClinicalKey, and Google Scholar. The keywords were Happy Hypoxia OR Silent Hypoxemia AND COVID-19 OR Coronavirus Disease. This literature study addresses potential pathways that may be associated with this interesting clinical feature. The hypothesis is that SARS-CoV-2 can cause nerve damage to the cortico-limbic tissue and alter dyspnoea perception and respiratory control. Future research will bring opportunities and advances in the study of the mechanism of hypoxia induced by COVID-19Key Words: Happy Hypoxia, Silent Hypoxemia, COVID-19, Coronavirus Disease.Â Â Abstrak: COVID-19 merupakan penyakit multifaset dengan kegagalan pernafasan sebagai manisfestasi yang umum. SARS-CoV-2 terutama menyerang sel epitel pernafasan melalui adhesi ke Angiotensin-Converting Enzyme 2 (ACE-2), pasien mengembangkan respon inflamasi ringan hingga parah dan cedera paru akut. Beberapa laporan menunjukkan banyak pasien menunjukkan upaya pernapasan dan dispnea yang lebih sedikit saat terkena gagal pernapasan akut dan hipoksemia, sebuah fenomena yang disebut â€œhappy hypoxiaâ€ atau â€œsilent hypoxemia